One of China's scholars the early life and conversion of Pastor Hsi - Taylor, Mary Geraldine, 1862-1949 (London, UK China Inland Mission, 1925)
Includes photographs.
Brethren writer. Two volumes in one : also contains : Pastor Hsi (of North China) : one of China's Christians, 1925.
Keywords: Hsi, Pastor, -- 1830-1896; Preachers -- China -- biography; Conversion to Christianity -- biography